Quality of information about liposuction for the lay public: A scoping review - Anderson Henrique da Silva Stahelin; Juan Carlos Montano Pedroso; André Hiroki Suyama Tsuji; Caroline Melo da Silva; Graziele Leite dos Santos; Felipe Contoli Isoldi; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: This scoping review aims to analyze the quality of information about liposuction for the lay public. Method: A literature search was carried out from November 18 to December 12, 2021, on the following database platforms: Medline, Cochrane, LILACS, Embase, and VHL. The search strategy involved the combination of several descriptors. Three independent investigators read the abstract of studies obtained using the search strategy to evaluate those that met the eligibility criteria. Results: Initially, 33 articles were collected using the search strategy. Among these, 23 studies were excluded after reading the abstracts and evaluating the eligibility criteria, as they did not have outcomes of interest to the proposed topic. Thus, ten studies met the inclusion criteria, nine of which were cross-sectional and one literature review. Among the ten articles included, nine report that information about liposuction is poor and inaccurate. Conclusion: The content on liposuction made available to the lay public via the Internet is, for the most part, unsatisfactory.